Analisis Perbandingan Prediksi Kebangkrutan Bank Syariah Dan Bank Konvensional Menggunakan Altman’s EM Z- Score Model - Agnes Anggun Minati; Gustati; Hidayatul Ihsan (Akuntansi dan Manajemen, 2016)
The development of Islamic banks in Indonesia increasingly shows that Islamic banks are ready to become competitors for conventional banks. Islamic banks that use margin systems or profit sharing whereas conventional banks use interest systems give rise to different expectations. It is possible to have a difference in terms of bankruptcy prediction using the Altman EM Z-Score Model ratio. The Altman EM Z-Score Model is a modification of the Altman ratio in 2002 that is used for non-manufacturing companies and has not gone public. This final project aims to analyze the comparison of predictions of bankruptcy of conventional Islamic banks and banks using Altman's EM Z-Score Model for the period 2012-2014. This type of research is descriptive comparative research. The sample used was 11 Islamic Commercial Banks and 23 Conventional Commercial Banks selected using the purposive sampling method. Data analysis techniques use different tests in whitney SPSS version 20. Based on the results of Z '' - Score shows that Indonesian banks are in a healthy state, but Islamic banks are more stable than conventional banks, while the results of whitney test show there are differences in working capital to total assets, retained earnings to total assets, EBIT to total assets, but there is no difference in the book value of equity to total liabilities of Islamic banks and conventional banks.